2020
DOI: 10.31883/pjfns/116611
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Microbial Quality of Stored Fermented Red Beetroots and Red Beetroot Juice

Abstract: The aim of this study was to investigate the effect of long-term cold storage of fermented beetroots and fermented beetroot juice on the content of biologically active compounds and microorganisms. Contents of total phenolics, as well as red and yellow betalains were determined. Total phenolics content in fermented grated beetroot was 920 mg/kg after 7 months of cold storage, while in juice it was 810 mg/L within the same timespan. At the end of the experiment, after 10 months of storage, these values decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 55 publications
6
26
2
Order By: Relevance
“…In the studies of Kazimierczak et al (2016), the level of these compounds in beetroot juice after fermentation process ranged between 37.3-123.3 mg•100 g -1 and depended on the cultivation method. Czyżowska et al (2020) found that the total phenolics content in the fermented beetroot of the cultivar 'Wodan F1' ranged from 920 mg•kg -1 after 7 months of cold storage and decreased to 570 mg•kg -1 after 10 months of storage. In our research, the level of betanin depended on the cultivar and was respectively: in 'Wodan F1' beetroots -0.11%, and in 'Alto F1' -0.17%.…”
Section: Resultsmentioning
confidence: 98%
“…In the studies of Kazimierczak et al (2016), the level of these compounds in beetroot juice after fermentation process ranged between 37.3-123.3 mg•100 g -1 and depended on the cultivation method. Czyżowska et al (2020) found that the total phenolics content in the fermented beetroot of the cultivar 'Wodan F1' ranged from 920 mg•kg -1 after 7 months of cold storage and decreased to 570 mg•kg -1 after 10 months of storage. In our research, the level of betanin depended on the cultivar and was respectively: in 'Wodan F1' beetroots -0.11%, and in 'Alto F1' -0.17%.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, the storage of beetroot juice at −80 • C during 32 days did not show changes, while samples stored at room temperature showed significant degradation of betacyanins [27]. The storage of fermented beetroot and beetroot juice at 5 • C during 7-10 months resulted in about 3-fold decrease of red pigments [28].…”
Section: Betalainsmentioning
confidence: 90%
“…Beetroot has a nutritive composition, with high amounts of dietary fiber [25] and high content of several biologically active compounds (Figure 1), including betalains (betacyanins and betaxanthins), carotenoids (β-Carotene, lycopene, and lutein), alkaloids (calystegine B1, calystegine B2, calystegine C1, calystegine B3, ipomine), glycosides, phenolic acids (ferulic acid, cafeic acid, syringic acid, p-coumaric acid, vanillic acid), flavonoids (rutin, rhamnetin, astragalin, rhamnocitrin, kaempferol), terpenoids (triterpenes and sesquiterpenoids), coumarins, saponins (oleanoic acid and several betavulgarosides), vitamins (A, E, K, C, B1-thiamine, B2-riboflavin, B3-niacin, B5-pantothenic acid, B6-pyridoxine, B9-folates, and B12-cyancobalamin), phytosterols, minerals (iron, phosphorous, potassium, calcium, manganese, magnesium, and selenium), and inorganic nitrate [10,21,[26][27][28]. Despite the high content of compounds that are of great interest to the meat industry, it must be borne in mind that the chemical and nutritional composition, as well as the content of bioactive compounds, depends on multiple factors [24].…”
Section: Phytochemicals Present In Beetrootmentioning
confidence: 99%
See 2 more Smart Citations